Effectiveness of extracorporeal shock wave therapy according to plantar calcaneal spur types (Annals of Medical Research, 2023)
Aim: The aim of this study is to group patients with plantar heel pain and calcaneal spurs detected via lateral foot x-rays based on the angle between the spur and the calcaneus and compare the efficacy of an Extracorporeal shock wave therapy (ESWT) treatment between these groups.Materials and Methods: The patients were divided into three groups based on the measurement the angle between the plantar calcaneal spur and the calcaneus. Those with a measured angle of 60° as Group 3. Demographic characteristics, spur length, visual analog scale (VAS) and foot function index score (FFI), and pain and function evaluation were used as the pre-and posttreatment data in each group.Results: Out of the 170 patients, 96 (56.5%) were included in Group 1, 65 (38.2%) were in Group 2, and 9 (5.3%) in Group 3. The posttreatment VAS and FFI scores of the patients were significantly lower than the pretreatment scores (p